A reforma da educação profissional: um estudo sobre o modelo de competências e suas implicações no plano de trabalho docente - Zaremba, Fellipe de Assis (2009)
This research aims to understand the impacts that the reform of professional education in teaching has produced within the State Center for Technological Education Paula Souza - CEETEPS. The choice of this network is because of their immediate accession to the fundamentals of reform, especially its appropriation of the so-called model of expertise. Defined as the search field to Júlio de Mesquita Technical School, founded in 1935 and, therefore, with a broad historical density. Our working hypothesis is that there is an intense process of mediation between what is announced by the reform and ownership in school, because this has produced a reform with very particular characteristics, demarcated by the culture and school practice. The sources of primary research is in the form of teaching plans, drawn up in the period 2004-2008, and in interviews with teachers and staff. The secondary sources are formed by the most important documents produced in the reform by various institutions, both federal and state government, besides those produced by CEETEPS. We check how the teaching of skills has impacted on the preparation of teaching plans and what are the implications of this process for the school culture and practice of the teacher.